Role of Exosomes in Central Nervous System Diseases - Liu, Wanying; Bai, Xiaodan; Zhang, Ao; Huang, Juanjuan; Xu, Shixin; Zhang, Junping (Frontiers in Molecular Neuroscience, 2019)
There are many types of intercellular communication, and extracellular vesicles are well known as one of the important forms of this. They are released by a variety of cell types, are heterogeneous, and they can be roughly divided into microvesicles and exosomes according to their occurrence and function. Of course, exosomes do not just play a role in cell-to-cell communication. In the nervous system, exosomes can participate in intercellular communication, maintain the myelin sheath, and eliminate waste. Similarly, exosomes in the brain can also play a role in central nervous system diseases, such as stroke, Alzheimer's disease (AD), Parkinson's disease (PD), prion disease, and traumatic encephalopathy (TBI), with both positive and negative effects (such as the transfer of misfolded proteins). From another point of view, exosomes contain a variety of key bioactive substances, and as such can be considered as a snapshot of the intracellular environment. Studies have shown that exosomes from the central nervous system can be found in cerebrospinal fluid and peripheral body fluids, and their contents will change with the occurrence of diseases. Because exosomes can penetrate the blood brain screen (BBB) and have high stability in the peripheral circulation, they can protect disease-related molecules very well and therefore using exosomes as a biomarker of central nervous system diseases is an attractive prospect, and they can be used to monitor the development of related diseases and enable early diagnosis and treatment optimization. In this review, we discuss the current state of knowledge of exosomes, and introduce their pathophysiological roles in different diseases of the central nervous system as well as their roles and applications as a viable pathological biomarker.